(untitled) (Fiep Bulletin - online, 2019)
This research aimed to analyze publications in the last six years emphasizing the recovery of moral and culturalvalues through games and games in school Physical Education classes, in the initial years of elementary education and how theycontribute to the formation of students in their citizenship, and to discuss how within the Corporal Culture the practice of playfulactivities such as games and games facilitates learning, and also rescues moral and cultural values that are transmitted betweenthe generations. It was a qualitative research, of the bibliographic type, which developed the from articles, published articles andofficial documents, where the search was done by the scielo and google academic database and journals, articles and / or bookswere selected that approach the theme, using keywords. The school is the second social group in that the child participates, in itnew experiences and discoveries arise and among these then the values social relations that are shared with the family, wherethis partnership will contribute to the formation of this new citizen, giving limits and being taught to reflect on the attitudes and theirconsequences. It is essential that the school awakens in students the capacity to understand and act in the world in which theylive, it is necessary to give them information and training so that they can act as citizens, organizing and defending their interestsand the collectivity. However, they need to learn to respect established rules, laws and norms (SOARES, 2012 apud FICAGNAand ORTH, 2010). Over the years, the school has undergone significant transformations, many parents are no longer asparticipative in the domestic education of their children. children and are not as participatory in school life, assigning the schoolthis role, transferring to teachers this function. Today the school does not only transmit knowledge for academic formation, butalso needs to guide the student’s formation as a citizen, passing on moral, social and ethical values. In this sense, PhysicalEducation contributes significantly. Physical Education is the curricular component that the maticises the corporal practices in itsdiverse forms of codification and social signification, understood as manifestations of the expressive possibilities of the subjects,produced by diverse social groups in the course of the history (BNCC, 2018). Popular games and games are activities that arecharacterized by flexible rules that can be changed or even created new rules collectively and that provide the pleasure of playingor playing, teaching with respect to rules.